The empirical link between relationship marketing tools and consumer retention in retail marketing - Bojei, Jamil; Julian, Craig C.; Che Wel, Che Aniza; Ahmed, Zafar U. (Wiley, 2013)
This article focuses on the key relationship marketing tools of customer service, loyalty/rewards programs, brand/store community, personalization and customization, and their relationship with customer retention. The relationship between customer service, loyalty/rewards programs, customization, personalization, brand/store community and customer retention were examined via an empirical investigation of 450 loyalty/reward program members of three retail stores in Malaysia. The administration of the survey was personally administered but self-completed. Four of the five relationship marketing tools, namely, customer service, loyalty/rewards programs, brand/store community and personalization, had a significant positive relationship with customer retention. The findings provided valuable insights into the loyalty program management practices of retail stores in a developing country context.